Benefit of glucosyl Hesperidin in patients with primary biliary cholangitis: A multicenter, open-label, randomized control study. Issue 48 (2nd December 2022) - Moriya, Kei; Asada, Kiyoshi; Suzuki, Shota; Enomoto, Masahide; Fujinaga, Yukihisa; Tsuji, Yuki; Namisaki, Tadashi; Yoshiji, Hitoshi
Abstract : Introduction: Globally, the number of patients with primary biliary cholangitis (PBC) is increasing. Growing evidence suggests that oxidative stress plays a significant role in the pathogenesis of chronic liver disease regardless of its etiology. Hesperidin, a natural antioxidative substance derived from citrus peel, has been shown to have an anti-inflammatory effect in a rat arthritis model and may be a potential substance to attenuate intrahepatic inflammation in patients with PBC. In this study, the potential of glucosyl hesperidin as a therapeutic agent for PBC will be investigated through antioxidative stress mechanisms. Methods: Patients with PBC who are 20 years or older will be eligible to participate. Patients will be assigned to 1 of 2 groups and given either 500 or 1000 mg of glucosyl hesperidin per day. The primary endpoint is the ratio of changes in serum gamma-glutamyl transferase levels before and after 24 weeks of glucosyl hesperidin administration. The secondary endpoints are serum hepatobiliary enzyme levels (alkaline phosphatase, transaminase, and total bilirubin levels) and the protein expression levels of nuclear factor erythroid 2-related factor 2 and its target molecule 8, 16, and 24 weeks after administration compared to before administration. Discussion: The prospective clinical interventional study was designed to assess the supportive effect of glucosyl hesperidin on hepatic function in patients with PBC receiving basic ursodeoxycholic acid treatment.